Nanosecond UV laser induced subsurface damage mechanics of cemented tungsten carbide. Issue 23 (1st December 2021) - Zhang, Quanli; Chu, Chenglong; Zhang, Zhen; Zhu, Yandan
Abstract: The subsurface damage in the laser machining process dramatically affects the mechanical properties and the service life of the cemented tungsten carbide. To further reveal the interaction mechanics, the subsurface damage characteristics of WC/8Co cemented carbide ablated by a nanosecond UV laser is explored through the angle polishing method, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) combined with focused ion beam (FIB) milling. The results show that severe cracking and crushing behaviors appear in the re-solidified areas and the heat-affected zone (HAZ). Based on the temperature field and stress field simulation results, the high temperature gradient induced thermal stress is responsible for the subsurface damage behavior. The blocking of the ablated groove caused by the solidification of the melted material is identified. The XPS spectrums indicate that the machined cemented tungsten carbide is seriously oxidized in the surface and to some extent in the subsurface layer, with the main oxidization products to be WO3, CoWO4, WO2, CoO and Co3 O4 . In addition, the deformation behavior of WC grain and the disordered alignment of Co atoms are identified in the re-solidified area and HAZ.